Personalidade e consumo ecologicamente consciente - Juliane de Almeida Ribeiro (2010)
In the last years, the increasing human levels of production and consumption have been discussed in different social areas in search of judicious ways for reducing the negative impacts they cause in the natural environment. Although high patterns of consumption are generally desired by all governments, business and countries, it is taking place at the same time the formation of a slow and gradual environmental consciousness in the field of consumption. Consumers are aware they can buy more ecologically friendly products, avoid natural resource wastes and do the recycling of their own garbage. Looking for ways consumers can be stimulated to increase their levels of suchenvironmental conscious behaviors, this research makes use of the 3M Model of Motivation and Personality (MOWEN, 2000) and of the Five Factor Model FFM (McCRAE; COSTA, 1997), to find the personality traits that are more connected to the execution and non execution of these behaviors. In a survey with 512 undergraduate students from different courses of a large Brazilian federal university, and exploratoryand confirmatory factorial analysis, being the lasts done with structural equation modeling, it was observed that consciousness, extroversion, openness to experience, altruism, self-efficacy, impulsiveness, frugality and consumerism presented significant associations with ecologically correct purchase, natural resources saving and recycling. Besides, there were obtained evidences of the 3M Models superior performance incomparison to the Five Factor Model. Even though the present research had been done with a students sample of a singular Brazilian university, we believe that it offers to business and governments useful information about the personality traits they should emphasize when elaborating publicity and propaganda pieces in the diverse communication medias, reinforcing, this way, the consumers awareness about the importance of practicing sustainable consumers behaviors.